Enhancing the effectiveness of strength training methods in the context of physical education for high school students - Astafyev V.S.; Gebert V.K.; Rudyakova I.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretical, methodological, and experimental validation of the approach to enhancing the strength capabilities of high school students through the application of fitness technologies. Methods and structure of the study. Twenty-two young men from the eleventh grade of Secondary School No. 26 in Chita, Transbaikal Territory, participated in a pedagogical experiment. The experiment, which consisted of three stages – ascertaining, forming, and control – was conducted from September 2023 to May 2024. During this time, medical and biological research was conducted, control tests were administered, and experimental methods were implemented. The boys in the control group (KG) and the experimental group (EG) engaged in the experiment for nine months, which were divided into three-week periods (mesocycles). Each mesocycle consisted of three weekly sessions (microcycles), each lasting 60 minutes outside of school hours. On average, 12 practical sessions were conducted in each mesocycle, resulting in a total of approximately 108 sessions. The sessions followed a structured format, with a warm-up (functional and joint warm-up), pre-stretch (dynamic stretching exercises) lasting 10 minutes, a cardio-power section (aerobic exercises for 25 minutes and strength training for 15 minutes), and a cool-down (static stretching exercises) lasting 10 minutes. Results and conclusions. The unique aspect of the experimental approach was the alteration of the content of the main lesson section by adjusting the level of physical exertion, employing the circuit method, alternating between aerobic and anaerobic activities, incorporating dynamic and static strength exercises, and integrating various types of strength training technologies with a gymnastic focus. The findings of the educational experiment confirmed the efficacy of the implemented approach. Based on the experimental outcomes, conclusions were drawn regarding the successful implementation of the method.